Circulating Tumor Cells: Finding Rare Events for A Huge Knowledge of Cancer Dissemination - Alix-Panabieres, Catherine (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The analysis of circulating tumor cells (CTCs) as a real-time liquid biopsy approach can be used to obtain new insights into metastasis biology, and as companion diagnostics to improve the stratification of therapies and to obtain insights into the therapy-induced selection of cancer cells. In this book, we will cover all the different facets of CTCs to assemble a huge corpus of knowledge on cancer dissemination: technologies for their enrichment, detection, and characterization; their analysis at the single-cell level; their journey as CTC microemboli; their clinical relevance; their biology with the epithelial-to-mesenchymal transition (EMT); their stem-cell properties; their potential to initiate metastasis at distant sites; their ex vivo expansion; and their escape from the immune system.